Mitotic diversity in homeostatic human interfollicular epidermis - Nöske, Katharina; Stark, Hans-Jürgen; Nevaril, Leonard; Berning, Manuel; Langbein, Lutz; Goyal, Ashish; Diederichs, Sven; Boukamp, Petra (International journal of molecular sciences, 2016)
Despite decades of skin research, regulation of proliferation and homeostasis in human epidermis is still insufficiently understood. To address the role of mitoses in tissue regulation, we utilized human long-term skin equivalents and systematically assessed mitoses during early epidermal development and long-term epidermal regeneration. We now demonstrate four different orientations: (1) horizontal, i.e., parallel to the basement membrane (BM) and suggestive of symmetric divisions; (2) oblique with an angle of 45°-70°; or (3) perpendicular, suggestive of asymmetric division. In addition, we demonstrate a fourth substantial fraction of suprabasal mitoses, many of which are committed to differentiation (Keratin K10-positive). As verified also for normal human skin, this spatial mitotic organization is part of the regulatory program of human epidermal tissue homeostasis. As a potential marker for asymmetric division, we investigated for Numb and found that it was evenly spread in almost all undifferentiated keratinocytes, but indeed asymmetrically distributed in some mitoses and particularly frequent under differentiation-repressing low-calcium conditions. Numb deletion (stable knockdown by CRISPR/Cas9), however, did not affect proliferation, neither in a three-day follow up study by life cell imaging nor during a 14-day culture period, suggesting that Numb is not essential for the general control of keratinocyte division.
Gesehen am 26.06.2020